Sosialisasi Motivasi Menulis Karya Fiksi Melalui Strategi Tiga Kata Kepada Mahasiswa di Asrama Ma’had Al-Jami’ah IAIN Palangka Raya - Sri Normuliati (Universitas Lambung Mangkurat, 2022)
Tujuan pengabdian ini untuk meningkatkan keterampilan menulis karya fiksi melalui strategi tiga kata kepada mahasiswa di asrama Ma’had Al-Jami’ah IAIN Palangka Raya. Pengabdian kepada masyarakat ini menggunakan media zoom meeting dengan membuka kesempatan kepada para mahasiswa untuk berdiskusi seputar menulis fiksi. Kegiatan ini dilaksanakan pada 3 Januari 2022 dan diikuti oleh 164 mahasiswa dari berbagai program studi di IAIN Palangka Raya. Metode yang digunakan dalam pengabdian ini adalah metode ceramah dan tanya jawab. Hasil yang didapatkan pada pengabdian ini menunjukkan bahwa permasalahan ketidaktahuan para mahasiswa dalam memulai menulis fiksi teratasi dengan menggunakan strategi tiga kata. Dalam pengabdian kepada masyarakat ini didapatlah beberapa poin kesimpulan, yaitu kesulitan menulis fiksi di kalangan mahasiswa dikarenakan mereka tidak tahu bagaimana mengolah ide dan bagaimana memulai sebuah cerita, faktor eksternal terutama dari lingkungan keluarga yang tidak mendukung aktivitas menulis, dan adanya keraguan untuk menekuni dunia menulis fiksi dikarenakan latar belakang mahasiswa yang bukan dari fakultas/prodi bahasa dan sastra. Dengan terbukanya mereka terhadap permasalahan yang dimiliki, terutama di faktor yang berhubungan dengan keterampilan menulis, maka menerapkan strategi tiga kata adalah cara yang dapat dilakukan. Strategi ini dapat membantu mahasiswa dalam meningkatkan keterampilan menulis fiksi. This service aims to improve fiction writing skills through a three-word strategy for students at the Ma'had Al-Jami'ah dormitory IAIN Palangka Raya. This community service uses the media zoom meeting by opening opportunities for students to discuss writing fiction. This activity was held on January 3, 2022, and was attended by 164 students from various study programs at IAIN Palangka Raya. The method used in this service is the lecture and question and answer method. The results obtained in this service indicate that the problem of students' ignorance in starting to write fiction is resolved by using a three-word strategy. In this community service, several conclusion points were obtained, namely the difficulty of writing fiction among students because they do not know how to process ideas and how to start a story, external factors, especially from the family environment that does not support writing activities. There are doubts about pursuing the world of writing fiction because of the background of students not from the faculty/study program of language and literature. With their openness to their problems, especially in factors related to writing skills, applying the three-word strategy is the way to go. This strategy can help students in improving their fiction writing skills.: This service aims to improve fiction writing skills through a three-word strategy for students at the Ma'had Al-Jami'ah dormitory IAIN Palangka Raya. This community service uses the media zoom meeting by opening opportunities for students to discuss writing fiction. This activity was held on January 3, 2022, and was attended by 164 students from various study programs at IAIN Palangka Raya. The method used in this service is the lecture and question and answer method. The results obtained in this service indicate that the problem of students' ignorance in starting to write fiction is resolved by using a three-word strategy. In this community service, several conclusion points were obtained, namely the difficulty of writing fiction among students because they do not know how to process ideas and how to start a story, external factors, especially from the family environment that does not support writing activities. There are doubts about pursuing the world of writing fiction because of the background of students not from the faculty/study program of language and literature. With their openness to their problems, especially in factors related to writing skills, applying the three-word strategy is the way to go. This strategy can help students in improving their fiction writing skills